PRETREATMENT TRAMETES VERSICOLOR DAN PLEUROTUS OSTREATUS PADA BAGAS UNTUK PRODUKSI BIOETANOL - Anita, Sita Heris; Fajriutami, Triyani; Fitria, -; Ermawar, Riksfardini Annisa; Yuli Yanto, Dede Heri; Hermiati, Euis (LIPI Press, 2011)
Single and mix cultures of white-rot fungi Trametes versicolor and Pleurotus ostreatus has been applied onto sugarcane bagasse as a pretreatment process. The purpose of this research was to investigate the effect of single and mix cultures of white-rot fungi in lignin degradation while maintaining minimum loss of ?-cellulose of sugarcane bagasse. Single and mix cultures of white-rot fungi T. versicolor and P. ostreatus have been inoculated onto sugarcane bagasse which varied in 5%, 10%, and 15% (w/v) with inoculum comparison 1:1. After 4-week incubation, analysis was carried out on the content of extractives, lignin, ?-cellulose and hemicellulose. The result showed that 4-week incubation of single culture of P. ostreatus was more advantageous as a pretreatment method for sugarcane bagasse, with considerable number of lignin degradation (17,95%) and minimum loss of cellulose (11,00%) and hemicelluloses (5,75%). As with mix cultures, incubation period should have been reduced to prevent significant loss of cellulose and hemicellulose. Furthermore, with shorter incubation period, this biological pretreatment process will be more interesting and feasible for the industry.